Pengaruh Manajemen Kepemimpinan terhadap Jalur Karier Keperawatan di Rumah Sakit: A Systematic Review - Novi Yulianti; Susanti Susanti (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Leadership management plays a crucial role in developing nursing career paths in hospitals. An effective career path system not only enhances nurses' competence and professionalism but also contributes to job satisfaction and retention. However, scientific evidence regarding the influence of leadership management on nurses' career paths remains scattered and shows varying findings. This systematic review aims to synthesize scientific evidence related to the influence of leadership management on nursing career path development in hospitals. This study used a systematic review design following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. A literature search was conducted through PubMed and Google Scholar for articles published between 2015 and 2024. Articles were selected based on inclusion and exclusion criteria, resulting in 13 articles for analysis. Data synthesis was conducted using a thematic synthesis approach. The review identified five main themes: leadership style, managerial support, organizational systems and policies, the impact of career paths, and barriers to implementation. Transformational and participatory leadership has been reported to have a positive influence on nurses' career development. Managerial support through coaching, mentoring, and ongoing training strengthens career readiness, increases job satisfaction, and reduces nurse turnover intentions. Leadership management has a significant influence on nursing career development in hospitals. Integrating effective leadership with a clear and transparent career development system is necessary to enhance professionalism, job satisfaction, and the sustainability of the nursing workforce.